Public policies of food security for the supply of corn. Venezuela (Period 2009-2019) (Revista Científica Compendium, 2022)
The objective of the study was to evaluate the public policies for the supply of the corn item in Venezuela (Period 2009-2019). It is an ex post-facto research, which used descriptive statistics for data analysis. Representatives of public institutions, union organizations, producers and researchers in the agricultural area make up the sources of information. One of the main conclusions establishes that some government actions included within the period under study did not achieve the proposed objectives. The optimization of the organizational structures, the increase of the control of the public management and the prioritization of the needs of the producers are recommended aspects.
Keywords: Food Security; Public Policies; Supply; Corn